2001
DOI: 10.1128/jb.183.12.3556-3563.2001
|View full text |Cite
|
Sign up to set email alerts
|

HreP, an In Vivo - Expressed Protease of Yersinia enterocolitica , Is a New Member of the Family of Subtilisin/Kexin-Like Proteases

Abstract: The role of proteases in pathogenesis is well established for several microorganisms but has not been described for Yersinia enterocolitica. Previously, we identified a gene, hreP, which showed significant similarity to proteases in a screen for chromosomal genes of Y. enterocolitica that were exclusively expressed during an infection of mice. We cloned this gene by chromosome capture and subsequently determined its nucleotide sequence. Like inv, the gene encoding the invasin protein of Y. enterocolitica, hreP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 60 publications
1
37
0
Order By: Relevance
“…Bacteria normalized to an optical density at 600 nm of 0.25 (corresponding to approximately 1.2 ϫ 10 6 bacteria) were resuspended in 4ϫ protein loading buffer, boiled, and separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Proteins were transferred to nitrocellulose membranes by Western blotting and incubated with an anti-HreP prosequence antiserum as described previously (19).…”
Section: Detection Of Hrep Expression By Western Blottingmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacteria normalized to an optical density at 600 nm of 0.25 (corresponding to approximately 1.2 ϫ 10 6 bacteria) were resuspended in 4ϫ protein loading buffer, boiled, and separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Proteins were transferred to nitrocellulose membranes by Western blotting and incubated with an anti-HreP prosequence antiserum as described previously (19).…”
Section: Detection Of Hrep Expression By Western Blottingmentioning
confidence: 99%
“…A further study characterizes hreP, which codes for a protease with similarity to eukaryotic subtilisin/kexin-like proteases. Y. enterocolitica hreP mutant strains have a defect in virulence in the mouse model of infection (19,44). The HreP protease is expressed as a proprotein, where the amino-terminal prosequence serves as an intramolecular chaperone, which is autocatalytically cleaved off after folding.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mutational analysis revealed a strong reduction of competitiveness and virulence of the hreP mutant (300). The HreP protease shows significant similarity with eukaryotic subtilisin/kexin-like proprotein convertases and was probably acquired by horizontal gene transfer (100). Although mutational studies unequivocally demonstrated the importance of HreP in virulence, its precise role has yet to be elucidated.…”
Section: Genes Involved In Central Intracellular Metabolismmentioning
confidence: 99%
“…(pYV) and five virulence genes (ail, ystA, ystB, myfA, hreP) and rfbC for O :3 serotype located in the chromosome [17][18][19][20]. The DNA was released from bacterial colonies by heating at 97 xC for 10 min, and 1 ml of this liquid was added to 19 ml of the mastermix (iQ TM SYBR Green Supermix ; Bio-Rad, USA).…”
Section: Further Strain Characterizationmentioning
confidence: 99%